Determining patterns in the formation of cordierite phase during the synthesis of density-sintered low-temperature ceramics based on glasses of the MgO–Al2O3–SiO2 system - Zaichuk, Oleksandr; Amelina, Aleksandra; Kalishenko, Yuliia; Hordieiev, Yurii (Eastern-European Journal of Enterprise Technologies, 2022)
The search for effective modifiers of the structure of densely baked cordierite ceramics to reduce the firing temperature is a relevant task but typically requires a large amount of experimental research. The object of this study is the reaction of the formation of the cordierite phase with the participation of glass components of the eutectic compositions of the MgO– Al2O3–SiO2 system under low-temperature firing conditions. In this case, thermodynamic analysis was used as a tool to assess the probability of chemical reactions. Thermodynamic analysis can significantly reduce the volume of the experimental sample. This paper reports the results of theoretical and experimental studies into the features of the course of chemical reactions with the participation of glass components of eutectic compositions of the MgO–Al2O3–SiO2 system. It was revealed that once the stoichiometric ratio is maintained, the resulting product of the interaction between the components of eutectic glasses of the MgO–Al2O3–SiO2 system with charging components is cordierite. Changes in the mineralogical composition of cordierite compositions depending on the firing temperature have been determined. The formation of the cordierite phase is preceded by the process of transformation of meta kaolinite Al2O3·2SiO2, which is a product of kaolin dehydration, into mullite 3Al2O3·2SiO2. Subsequently, the formation of cordierite (in addition to crystallizing directly from eutectic glasses) occurs with the participation of the mullite phase. The formation of the cordierite phase occurs in several stages and is completed at a temperature of 1300 °C. The established features of the reactions of cordierite formation make it possible to determine the most optimal compositions for glasses of the MgO–Al2O3–SiO2 system to obtain low-temperature cordierite ceramics with a high degree of sintering. At the same time, it is also possible to control the phase composition of ceramics and its properties